Unlocking Bangladesh-India Trade : Emerging Potential and the Way Forward - De, Prabir; Raihan, Selim; Kathuria, Sanjay (World Bank, Washington, DC, 2012)
The primary objective of this study is to analyze the impact on Bangladesh of increased market access in India, both within a static production structure and also identifying dynamic gains. The study shows that Bangladesh and India would both gain by opening up their markets to each other. Indian investments in Bangladesh will be very important for the latter to ramp up its exports, including products that would broaden trade complementarity and enhance intra-industry trade, and improve its trade standards and trade-handling capacity. A bilateral Free Trade Agreement would lift Bangladesh's exports to India by 182 percent, and nearly 300 percent if transaction costs were also reduced through improved connectivity. These numbers, based on existing trade patterns, represent a lower bound of the potential increase in Bangladesh's exports arising from a Free Trade Agreement. A Free Trade Agreement would also raise India's exports to Bangladesh. India's provision of duty-free access for all Bangladeshi products (already done) could increase the latter's exports to India by 134 percent. In helping Bangladesh's economy to grow, India would stimulate economic activity in its own eastern and north-eastern states. Challenges exist, however, including non-tariff measures/barriers in both countries, excessive bureaucracy, weak trade facilitation, and customs inefficiencies. Trade in education and health care services offers valuable prospects, but also suffers from market access issues. To enable larger gains, Bangladesh-India cooperation should go beyond goods trade and include investment, finance, services trade, trade facilitation, and technology transfer, and be placed within the context of regional cooperation.